Intention to Invest in Islamic Capital Market Among Youth: The Influence of Sharia Financial Literacy and Religiosity - Ja'far, Achmad Mu'afi; Julaihah, Umi; Adenina Zidni Maulida, Nabila (MALIA: Jurnal Ekonomi Islam, 2025)
Introduction: According to the National Survey of Financial Literacy and Inclusion conducted in 2019, the number of Islamic stocks and Islamic capital market assets has increased in Indonesia, but the level of Islamic financial literacy and Islamic capital markets of the Indonesian population is still very low compared to conventional ones. This study aims to determine the effect of Islamic financial literacy and religiosity on investment interest in the Islamic capital market. Methods: This research employed quantitative methods with regression analysis. Data were collected using a questionnaire through Google Forms, resulting in a sample of 203 students in Malang, Indonesia. Results: The results showed that, either partially or simultaneously, Sharia financial literacy and religiosity variables had a significant positive effect on investment intention in the Islamic capital market. Moreover, it had a high coefficient determination of about 0.752, indicating that the financial literacy and religiosity variables can influence the investment intention variable by 75.2%. Conclusion and suggestion: Based on the findings, it was demonstrated that religiosity had a greater impact on the intention to invest in the Islamic capital market compared to Sharia financial literacy. This could be due to the fact that the level of Sharia financial literacy among respondents remains low. Thus, to boost young participation in the Islamic capital market, it is recommended that academic institutions educate young people about Sharia financial literacy through formal education. Also, the businesses could provide informal information about investing in the Islamic capital market.